THE IMPLEMENTATION OF E-LEARNING IN TEACHING ENGLISH AT SMP NEGERI 1 OF BANYUASIN III - Rizky Amalia; Tahrun Tahrun; Mulyadi Mulyadi (Esteem Journal of English Education Study Programme, 2023)
This study focused on the utilization of E-Learning in English language instruction at SMP Negeri 1 of Banyuasin III. The study aimed to achieve three objectives: 1) identify the E-Learning media employed by teachers in English teaching; 2) examine the implementation of E-Learning applications by teachers in English instruction; and 3) investigate the challenges encountered by both teachers and students in utilizing E-Learning media for English learning. The research methodology employed was qualitative-descriptive, which involved data collection through observation, interviews, and documentation. The findings of the study revealed the following: 1) Google Classroom and YouTube were utilised as learning platforms; 2) the implementation of E-Learning in English instruction involved three stages: planning, implementation (including opening, core activities, and closing), and evaluation; 3) the major challenges faced by teachers included a lack of technological resources and difficulties in assessing student comprehension in the E-Learning environment; and 4) students encountered challenges related to distractions from other applications and difficulties in social interaction within the E-Learning setting.